Public administration and the modern state : assessing trends and impact - Bohne, Eberhard; Graham, John D.; Raadschelders, Jos C. N.; Lehrke, Jesse Paul.; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
The challenges faced by the public sector are many and varied. Civil services at the forefront of tackling pressing problems in a whole range of areas from climate change to income inequality are being allocated less money to do so. This collection explores how public sectors have adapted to address the demands placed on them in the 21st Century.
Keywords: Political science; Political theory; Comparative politics; Public policy; Globalization; Public administration